Senator John F. Kennedy is a friend of the algerian revolution through his speech to congress on july 2, 1957 - belalia, Miloud (The Algerian Historical Journal, 2026)
This article aims to shed light on the position of us senator John F. Kennedy towards the algerian revolution through his speech to congress on july 2, 1957, on the eve of his country's celebration of the american revolution. The content of this speech from the chairman of the congressional foreign affairs committee is analyzed contrary to the us administration's biased policy towards colonial France. This speech was the most influential in world public opinion. Kennedy condemned french colonial policy in Algeria and criticized his country's position in support of France in its war against Algeria, calling for algerian independence. In this article, we conclude that senator John F. Kennedy's early friendship with the algerian revolution was the result of several factors, including the character of this American from the origins of a catholic immigrant family from Ireland that suffered british persecution, and the role of the media office of the National Liberation Front in New York and washington in making algeria's voice heard in western and especially american public opinion.